Analyze the Impact of Reducing Gender Inequality on Socio-Economic Value - Liang, Wenlin (Transactions on Economics, Business and Management Research, 2024)
This paper examined Unilever’s strategy for enhancing the livelihoods of female Ivorian cocoa farmers, focusing on the research question of how a Fast-Moving Consumer Goods (FCMG) company can strike a balance between reducing gender inequality and boosting economic value. One of the seventeen Sustainable Development Goals (SDGs) is to reduce gender inequality. This issue is especially prevalent among Côte d’Ivoire’s female cocoa farmers. The purpose of this study was to identify the three methods for resolving this issue. It started with giving women farmers easier access to resources for education and training, followed by an increase in the number of women in leadership roles and more collaborations with stakeholders. Unilever leads the industry in corporate social responsibility, conducting extensive research by examining the company’s current policies and action plans. However, future recommendations suggest integrating technology, adhering to the law, and anticipating improved legal frameworks and integrated networks that work together to create a sustainable society.